ダイナミック・ケイパビリティ論からペンローズへ - 岩尾 俊兵; 菊地 宏樹 (Akamon Management Review, 2016)
This technical note tackles to put ill-ordered research stream about Dynamic Capabilities (DC) to right. From research review, we could see theories on DC are now in confusion, and some weighty counters are attacking prior study of DC (e.g., Teece’s ideas). In this paper, Helfat and Winter (2011) is commented. Furthermore, this paper points out that Helfat and Winter’s research closely resemble Penrose’s idea about the growth of the firms. If we try to understand DC theory from Penrose’s idea, we will learn about DC more easily. ダイナミック・ケイパビリティについて、多数の論者から多様な定義が行われてきた。しかし、「劇的な環境変化に対応する能力」というTeece流の代表的なDC定義下では、DCと業務能力を客観的に分離し研究するのが困難であるという指摘が、近年HelfatとWinterによってなされている。Helfat and Winter (2011) による上記の指摘とそれを乗り越えるための処方箋は、DCを単純に企業成長の源泉として捉え直すというものだと考えてよい。彼女らの論点は、その意味で、エディス・T・ペンローズの『企業成長の理論』の観点との類似点を見出しうる。